S4 Relationship Between Historic Uk Asbestos Imports And Annual Mortality Due To Mesothelioma, Asbestosis And Idiopathic Pulmonary Fibrosis. (10th November 2014) - Barber, CM; Wiggans, RE; Fishwick, D
Abstract : Background: Previous studies from a number of countries have demonstrated that the rising mortality due to mesothelioma and asbestosis can be predicted from their historic asbestos usage. Mortality due to idiopathic pulmonary fibrosis (IPF) is also rising in the UK, without any identified explanation. This analysis compared annual male and female mortality due to IPF, asbestosis and mesothelioma, and examined the relationship between mortality and national asbestos import data. Methods: Mortality data for IPF and asbestosis in England and Wales were available from the Office for National Statistics (ONS). Data for mesothelioma deaths in England and Wales and historic UK asbestos import data were available from the Health and Safety Executive (HSE). The numbers of annual deaths due to each condition were plotted separately by gender, against UK asbestos imports 48 years earlier. Pearson correlation co-efficients were then calculated. Results: Correlation co-fficients for each condition are shown in Table 1 . The annual number of deaths due to mesothelioma and IPF were significantly correlated with historical asbestos imports for both genders. For asbestosis mortality, a similar relationship was found for male but not female deaths. Conclusion: The strength of the association between IPF and historical asbestos imports was similar to that seen for mesothelioma mortality. This finding suggests that the role of occupational and environmental asbestos exposure in the aetiology of IPF requires further consideration.